An integrative taxonomic revision of the genus Triphosa Stephens, 1829 (Geometridae: Larentiinae) in the Middle East and Central Asia, with description of two new species - Wanke, Dominic; Hausmann, Axel; Rajaei, Hossein (Zootaxa, 2019)
Western Palaearctic species of the genus Triphosa Stephens, 1829 are revised with focus on the Middle East and Central Asia. The analysis is based on the morphological examination (wing pattern and genitalia) of the type series of most species, as well as of large series of additional material. Additionally, DNA barcode data were used as an extra line of information. As result, Triphosa agnata Le Cerf, 1918 syn. n. is synonymized with T. sabaudiata (Duponchel, 1830), the taxonomy of the enigmatic Triphosa taochata Lederer, 1870 is clarified, and two species are described as new to science: T. silviae sp. n. and T. lecerfi sp. n.. Hydria ravulata (Staudinger, 1892) comb. rev., is transferred from Triphosa to the genus Hydria. Lectotypes are designated for Triphosa taochata and Hydria ravulata. Wing pattern, genitalia and diagnostic characters of all examined species are illustrated and the distribution data shown on the map.